Very-High Color Rendering Index Hybrid White Organic Light-Emitting Diodes with Double Emitting Nanolayers - Liu, Baiquan; Xu, Miao; Wang, Lei; Tao, Hong; Su, Yueju; Gao, Dongyu; Lan, Linfeng; Zou, Jianhua; Peng, Junbiao (Nano-Micro Letters, 2014)
A very-high color rendering index white organic light-emitting diode (WOLED) based on a simple structure was successfully fabricated. The optimized device exhibits a maximum total efficiency of 13.1 and 5.4 lm/W at 1,000 cd/m2. A peak color rendering index of 90 and a relatively stable color during a wide range of luminance were obtained. In addition, it was demonstrated that the 4,4′,4″-tri(9-carbazoyl) triphenylamine host influenced strongly the performance of this WOLED. These results may be beneficial to the design of both material and device architecture for high-performance WOLED.